2012
DOI: 10.1084/jem.20121076
|View full text |Cite
|
Sign up to set email alerts
|

B cell survival, surface BCR and BAFFR expression, CD74 metabolism, and CD8− dendritic cells require the intramembrane endopeptidase SPPL2A

Abstract: Mice lacking activity of the intramembrane protease SPPL2A exhibit humoral immunodeficiency and lack mature B cell subsets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
97
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 40 publications
6
97
0
Order By: Relevance
“…Furthermore, functionality of the remaining B cells is considerably impaired with regard to Ig production. Major phenotypic findings described in this study were additionally confirmed in two SPPL2a mutant mouse lines (19,20). Additional ablation of CD74 in SPPL2a 2/2 mice improved B cell maturation and function, indicating that the B cell phenotype of these mice can be mainly ascribed to the incomplete turnover of the CD74 NTF (13).…”
supporting
confidence: 72%
“…Furthermore, functionality of the remaining B cells is considerably impaired with regard to Ig production. Major phenotypic findings described in this study were additionally confirmed in two SPPL2a mutant mouse lines (19,20). Additional ablation of CD74 in SPPL2a 2/2 mice improved B cell maturation and function, indicating that the B cell phenotype of these mice can be mainly ascribed to the incomplete turnover of the CD74 NTF (13).…”
supporting
confidence: 72%
“…The Zfp318 point mutant strain was identified by flow cytometry screening of peripheral blood lymphocytes in third-generation offspring from ENU-treated C57BL/6 mice as described (39). Identification of the causal mutation was done by whole exome sequencing as described (40,41). The Zfp318 −/− mice were generated by H.H.…”
Section: Methodsmentioning
confidence: 99%
“…This requires cathepsin S (Riese et al 1996;Driessen et al 1999;Nakagawa et al 1999;Shi et al 1999) or cathepsins L and F (Nakagawa et al 1998;Shi et al 2000), depending on the cell type. Degradation of the remaining transmembrane fragment requires the intramembrane endopeptidase SPPL2A (Beisner et al 2013;Bergmann et al 2013;Schneppenheim et al 2013). Although early studies proposed that Ii degradation is regulated and enhanced in response to DC activation (Pierre and Mellman 1998), subsequent studies proved that Ii processing is a constitutive process and not rate limiting for antigen presentation by MHCII (Villadangos et al 2001(Villadangos et al , 2005El-Sukkari et al 2003;ten Broeke et al 2010).…”
Section: Biosynthesis Of Mhciimentioning
confidence: 99%